Study on Dynamic Response of Inclined Pile Group Foundation under Earthquake Action - Weihong Huang; Jiankun Liu; Heng Wang; Mo’men Ayasrah; Hongsheng Qiu; Zhuofan Wang (Buildings, 2023)
With the development of all types of new special-shaped arch bridges, the deformation of the pile foundation of special-shaped steel arch bridges has a great influence on the superstructure, and the requirements for it are strict. In addition, the force of the inclined pile group under an earthquake is complicated. In this paper, based on the Zhuhai Jindao Bridge project, the finite element numerical model is established in order to study the dynamic response and parameter influence law of an inclined straight pile group foundation under earthquake action. After a thorough analysis of the results of the simulation, it was found that under the action of an earthquake, the inclination angle of inclined piles has a significant influence on the seismic ability of pile group foundations. When the inclination angle of an inclined pile is 5°, the ability of the inclined pile group foundation to resist deformation can be effectively improved, and the load distribution of the pile top is more reasonable.